I gathered as a policy of expansion of federal universities and the cuts of the Federal Government (Research, Society and Development, 2020)
This work aims to highlight the importance and reflect on an educational public policy, showing its respective results, highlighting public problems, highlighting its actors and classifying the policy chosen in the typologies of the following theorists: Lowi, Wilson, Gormley, Gustafsson, Bozeman and Pandey. The public policy that we will discuss in this paper is the Support Program for Academic Restructuring and Expansion Plans at Federal Universities (REUNI), created in the government of ex-president Luiz Inácio Lula da Silva, in 2007, the objective of this public policy focused on the area of education was to create conditions for the expansion of access and permanence in higher education. After studies, it was observed that the majority of Federal universities were located in the capitals and low-income students from the interiors did not obtain access to higher education, nor were they able to maintain themselves in the capitals, so the main focus of this policy is the internalization of federal universities and ifes as an expansion of access and permanence in higher education.